Riesgos ergonómicos-biomecánicos de orígen laboral en relación con la salud del personal de enfermería que labora en el Áärea de Cirugía y Quimiotterapia, del Hospital de Solca-Loja, marzo-septiembre 2013. - Espinoza García, Silvana de Lourdes (2014)
This research aims to identify ergonomic risk factors - biomechanical work-related health problems in nurses working in the area of surgery and chemotherapy SOLCA hospital-Loja; research was supported, under the type of descriptive study, the universe was formed, 17 nurses and 11 nursing auxiliaries people, all 28; instruments used were a survey and checklist. The research results indicate that in the studied group, females have higher prevalence, most professional staff works with seniority greater than 10 years; risks found were: overweight and obesity, lack of knowledge about biomechanics ergonomics, handling loads greater than 25kg weight, no rest periods during the workday, the position it most of the time is prolonged standing, made efforts the care and management of patients with a frequency higher than five times; concerning the muscle-skeletal alterations to cervical, thoracic and lumbar levels were found; level lower limbs, stiffness and pain in the knee joints, edema, muscle tension and presence of variz; relating to furniture, beds have mechanical, manual wheel chairs impaired controls; regarding body mechanics, there is a partial application. The results of the study led to the development of self-care education activities to help reduce the incidence of-biomechanical ergonomic risks of nurses, the same who had a favorable response. Keywords: ergonomics biomechanics. Occupational hazard. Body mechanics